Development of F1 hybrids resistance to bacterial wilt incidence in tomato (Solanum lycopersicum L.) - R.P. Jaiprakashnarayan; S.B. Mallesh; M.G. Patil and; Kushal (Electronic Journal of Plant Breeding, 2016)
Maximum heterosis over standard parent in desirable direction was 102.80 per cent (TP44 x TP40) for equatorial diameter of fruit, 67.30 per cent (TP44x TP40) for average fruit weight, 22.70 per cent (TP24 x TP40) for number of fruits per plant and 70.56 per cent (TP5 x TP29) for total yield per plant. A total of 15 crosses exhibited negative and significant heterosis over better parent for bacterial wilt incidence .The cross TP50 x TP25 for equatorial diameter of fruit; TP45x TP25 for average fruit weight; TP24 x TP40 for bacterial wilt, number of fruits per plant and total yield per plant were identified as good specific combiners. The parents TP45 and TP44 for equatorial diameter of fruit; TP5, TP24 and TP27 for bacterial wilt; TP45 and TP44 for average fruit weight; TP27 and TP24 for number of fruits per plant and TP44 for total yield per plant were identified as good general combiners. Non additive gene action was predominant for plant height at 90 DAT, days to 50 per cent flowering, equatorial diameter of fruit, bacterial wilt, average fruit weight and total yield per plant.